The Effect of Liquidity Risk, Financing Risk, and Operational Risk toward Indonesian Sharia Bank’s Financing with Bank Size as a Moderating Variable - Dea Prastica Alsyahrin; Apriani Dorkas Rambu Atahau; Robiyanto Robiyanto (Journal of Economics, Business, and Accountancy Ventura, 2018)
Islamic banking is growing rapidly in Indonesia, so it needs to be done a lot of studies on sharia banking especially about the influence of risks to sharia financing. The purpose of this study is to analyze of the influence of liquidity risk, financing risk, and operational risk with bank size as moderating variable. This research uses financial statement of Sharia Commercial Bank for 2012-2016 period. By using purposive sampling method, 12 Sharia Commercial Bank were chosen as samples in this study. The data use in this study is panel data. Those data was collected from Sharia Commercial Bank’s website. Data analyzed by using moderated regression analysis. The result shows that liquidity risk, financing risk, and operational risk significantly influenced the financing of Indonesian sharia banking with bank size as it’s moderating variable.